2015
DOI: 10.3389/fneur.2015.00016
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Deep Transcranial Magnetic Stimulation Sessions are Associated with Reduced Depressive Relapses in Patients with Unipolar or Bipolar Depression

Abstract: Introduction: Deep transcranial magnetic stimulation (dTMS) is a new form of TMS allowing safe stimulation of deep brain regions. The objective of this preliminary study was to assess the role of dTMS maintenance sessions in protecting patients with bipolar disorder (BD) or recurrent major depressive disorder (MDD) from developing depressive or manic relapses in a 12-month follow-up period.Methods: Twenty-four drug-resistant patients with a current depressive episode and a diagnosis of MDD or BD have been enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
0
25
0
2
Order By: Relevance
“…While cTBS is used to inhibit certain brain regions, other TMS protocols could be applied to improve the access to bodily sensations and empower concomitant therapeutic approaches as demonstrated for various disorders, e.g. in the decrease of relapse rates in depression [73]. More clinical research is needed to further elucidate future therapeutic avenues.…”
Section: Discussionmentioning
confidence: 99%
“…While cTBS is used to inhibit certain brain regions, other TMS protocols could be applied to improve the access to bodily sensations and empower concomitant therapeutic approaches as demonstrated for various disorders, e.g. in the decrease of relapse rates in depression [73]. More clinical research is needed to further elucidate future therapeutic avenues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a reduction of nicotine [20] and alcohol craving after cycles of deep transcranial magnetic stimulation (dTMS) over bilateral DLPFC [21][22][23]. In addition, a single session of repetitive TMS (rTMS) over the right DLPFC significantly reduced cocaine craving, a reduction that persisted four hours after the end of the session [7].…”
Section: Introductionmentioning
confidence: 94%
“…One study reported reduced relapse rate with continued maintenance TMS two times weekly and then weekly. The results suggested that maintenance TMS might be helpful in preventing affective episode relapses in a 12-month follow-up period (69).…”
Section: Transcranial Magnetic Stimulation Tms In Major Depressive DImentioning
confidence: 93%